2021
DOI: 10.7554/elife.60454
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between fast and slow oscillator circuits in Cancer borealis is temperature-compensated

Abstract: Coupled oscillatory circuits are ubiquitous in nervous systems. Given that most biological processes are temperature sensitive, it is remarkable that the neuronal circuits of poikilothermic animals can maintain coupling across a wide range of temperatures. Within the stomatogastric ganglion (STG) of the crab, Cancer borealis, the fast pyloric rhythm (~1Hz) and the slow gastric mill rhythm (~0.1Hz) are precisely coordinated at ~11°C such that there is an integer number of pyloric cycles per gastric mill cycle (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 107 publications
2
49
4
Order By: Relevance
“…Thus, different modulators can elicit different dynamical mechanisms of rhythm generation. In support of this hypothesis, it has been reported that similar gastric mill rhythms, which are generated by a stimulation of disparate neuromodulatory pathways, have different temperature sensitivity ( Powell et al, 2021a ; Städele et al, 2015 ). A modest temperature increase of 3°C abolishes the MCN1-rhythm ( Städele et al, 2015 ), in contrast, the VCN-rhythm is temperature-robust over a wide range of temperatures, between 7°C and 25°C ( Powell et al, 2021a ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, different modulators can elicit different dynamical mechanisms of rhythm generation. In support of this hypothesis, it has been reported that similar gastric mill rhythms, which are generated by a stimulation of disparate neuromodulatory pathways, have different temperature sensitivity ( Powell et al, 2021a ; Städele et al, 2015 ). A modest temperature increase of 3°C abolishes the MCN1-rhythm ( Städele et al, 2015 ), in contrast, the VCN-rhythm is temperature-robust over a wide range of temperatures, between 7°C and 25°C ( Powell et al, 2021a ).…”
Section: Discussionmentioning
confidence: 82%
“…In support of this hypothesis, it has been reported that similar gastric mill rhythms, which are generated by a stimulation of disparate neuromodulatory pathways, have different temperature sensitivity ( Powell et al, 2021a ; Städele et al, 2015 ). A modest temperature increase of 3°C abolishes the MCN1-rhythm ( Städele et al, 2015 ), in contrast, the VCN-rhythm is temperature-robust over a wide range of temperatures, between 7°C and 25°C ( Powell et al, 2021a ). We propose that the difference in temperature sensitivity between the two versions of the gastric mill rhythm could be explained by the differences in their dynamical mechanisms of oscillation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The coordination of the activities of coupled neural networks at different temperatures is particularly challenging, but often required for proper behavioral functioning. Powell et al (2021) have recently demonstrated that the coordination between two oscillatory circuits in the stomatogastric nervous system (STNS, Figure 1A ) of the crab Cancer borealis is maintained across a broad range of temperatures (7–23°C). The gastric mill and pyloric central pattern generators (CPGs) are coupled, but these rhythms run at very different speeds ( Nadim et al, 1998 ; Bartos et al, 1999 ; Stein, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…PD spikes were identified from pdn , intracellular recordings, and lvn . We used a custom-designed spike identification and sorting software (called ‘crabsort’) that we have made freely available at https://github.com/sg-s/crabsort (copy archived at swh:1:rev:6a67e765e90caa536e6a11f67d9d4737d059af50 ; Gorur-Shandilya, 2021 ), previously described in Powell et al, 2021 . Spikes are identified using a fully connected neural network that learns spike shapes from small labeled datasets.…”
Section: Methodsmentioning
confidence: 99%